Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Photo-Fenton degradation of the pharmaceuticals ciprofloxacin and fluoxetine after anaerobic pre-treatment of hospital effluent - João A. de Lima Perini; Beatriz Costa e Silva; Adriano L. Tonetti; Raquel F. Pupo Nogueira (Environmental Science and Pollution Research, 2017)

Unraveling Landscape Complexity: Land Use/Land Cover Changes and Landscape Pattern Dynamics (1954–2008) in Contrasting Peri-Urban and Agro-Forest Regions of Northern Italy - D. Smiraglia; T. Ceccarelli; S. Bajocco; L. Perini; L. Salvati (Environmental Management, 2015)

Effects of soil tillage on Tuber magnatum development in natural truffières - E. Salerni; M. Iotti; P. Leonardi; L. Gardin; M. D’Aguanno; C. Perini; P. Pacioni; A. Zambonelli (Mycorrhiza, 2014)

Erratum to: Land Use, Climate and Transport of Nutrients: Evidence Emerging from the Lake Vico Case Study - F. Recanatesi; M. N. Ripa; A. Leone; L. Perini; L. Salvati (Environmental Management, 2013)

Wild and cultivated mushrooms as a model of sustainable development - D. Donnini; M. L. Gargano; C. Perini; E. Savino; C. Murat; S. Di Piazza; E. Altobelli; E. Salerni; A. Rubini; G. L. Rana; M. Bencivenga; R. Venanzoni; et al. (Plant Biosystems, 2013)

Interactions of fungi with other organisms - S. Perotto; P. Angelini; V. Bianciotto; P. Bonfante; M. Girlanda; T. Kull; A. Mello; L. Pecoraro; C. Perini; A. M. Persiani; A. Saitta; S. Sarrocco; et al. (Plant Biosystems, 2013)

Molecular identification of root fungal associates in Orchis pauciflora Tenore - L. Pecoraro; M. Girlanda; T. Kull; C. Perini; S. Perotto (Plant Biosystems, 2012)

The Impact of Land Use/Land Cover Changes on Land Degradation Dynamics: A Mediterranean Case Study - S. Bajocco; A. De Angelis; L. Perini; A. Ferrara; L. Salvati (Environmental Management, 2012)

Fungal biodiversity and in situ conservation in Italy - G. Venturella; E. Altobelli; A. Bernicchia; S. Di Piazza; D. Donnini; M. L. Gargano; S. P. Gorjòn; V. M. Granito; A. Lantieri; D. Lunghini; A. Montemartini; F. Padovan; et al. (Plant Biosystems, 2011)

Color Vision in Leontopithecus chrysomelas: A Behavioral Study - Daniel M. A. Pessoa; Eduardo S. Perini; Lvia S. Carvalho; Carlos Tomaz; Valdir F. Pessoa (International Journal of Primatology, 2005)

Chemical and isotopic (C, O, Sr, Nd) characteristics of the Xiluvo carbonatite (central-western Mozambique) - P. Censi; G. Perini; L. Vasconcelos; V. Morra; F. Guerreiro; L. Bennio; L. Melluso (Mineralogy and Petrology, 2004)